2021
DOI: 10.1021/acsmedchemlett.1c00437
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gp120 Residue His105 as a Novel Target for HIV-1 Neutralization by Small-Molecule CD4-Mimics

Abstract: The design and synthesis of butyl chain derivatives at the indane ring 3-position of our lead CD4-mimetic compound BNM-III-170 that inhibits human immunodeficiency virus (HIV-1) infection are reported. Optimization efforts were guided by crystallographic and computational analysis of the small-molecule ligands of the Phe43 cavity of the envelope glycoprotein gp120. Biological evaluation of 11−21 revealed that members of this series of CD4-mimetic compounds are able to inhibit HIV-1 viral entry into target cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…While it is becoming increasingly clear that HIV-1 successfully evades nnAbs responses by keeping its Env in a “closed” conformation (Bruel et al, 2017; Dufloo et al, 2020; Veillette et al, 2015; Veillette et al, 2014; von Bredow et al, 2016), new strategies are currently being tested to harness their potential antiviral activity. Small CD4 mimetic compounds have been optimized to “open up” Env trimers, therefore exposing otherwise occluded epitopes recognized by nnAbs (Ding et al, 2019b; Fritschi et al, 2021; Jette et al, 2021; Laumaea et al, 2020; Melillo et al, 2016). Using this strategy, CD4mc were shown to synergize with monoclonal CD4i Abs or nnAbs found in plasma from infected individuals to eliminate HIV-1-infected cells in vitro , ex vivo and in vivo in humanized mice (Alsahafi et al, 2019; Anand et al, 2019; Ding et al, 2016b; Lee et al, 2015; Madani et al, 2018; Prevost et al, 2020b; Rajashekar et al, 2021; Richard et al, 2016; Richard et al, 2017; Richard et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…While it is becoming increasingly clear that HIV-1 successfully evades nnAbs responses by keeping its Env in a “closed” conformation (Bruel et al, 2017; Dufloo et al, 2020; Veillette et al, 2015; Veillette et al, 2014; von Bredow et al, 2016), new strategies are currently being tested to harness their potential antiviral activity. Small CD4 mimetic compounds have been optimized to “open up” Env trimers, therefore exposing otherwise occluded epitopes recognized by nnAbs (Ding et al, 2019b; Fritschi et al, 2021; Jette et al, 2021; Laumaea et al, 2020; Melillo et al, 2016). Using this strategy, CD4mc were shown to synergize with monoclonal CD4i Abs or nnAbs found in plasma from infected individuals to eliminate HIV-1-infected cells in vitro , ex vivo and in vivo in humanized mice (Alsahafi et al, 2019; Anand et al, 2019; Ding et al, 2016b; Lee et al, 2015; Madani et al, 2018; Prevost et al, 2020b; Rajashekar et al, 2021; Richard et al, 2016; Richard et al, 2017; Richard et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…the α1 and α5 helices (Figure 1B). As a result, some 3-substituted indane analogs, such as CJF-III-049-S (2, Figure 1C), exhibited modest (3-fold) improvements in antiviral activity compared with BNM-III-170; however, only the viruses with His 105 in the gp120 α1 helix showed such an increase (40). Based on the above observations, we hypothesized that replacing the C3 carbon with a nitrogen (Figure 1A and C) to create an indoline scaffold might have several benefits.…”
mentioning
confidence: 99%
“…Guided by crystal structures of BNM-III-170 and congeners thereof, we found that 3-substituents on the indane ring of BNM-III-170 can contact a vestibule pocket situated at the interface of the gp120 inner and outer domains, between the α1 and α5 helices (Figure 1B). As a result, some 3-substituted indane analogs, such as CJF-III-049-S (2, Figure 1C), exhibited modest (3-fold) improvements in antiviral activity compared with BNM-III-170; however, only the viruses with His 105 in the gp120 α1 helix showed such an increase (40). Based on the above observations, we hypothesized that replacing the C3 carbon with a nitrogen (Figure 1A and C) to create an indoline scaffold might have several benefits.…”
mentioning
confidence: 99%
“…While it is becoming increasingly clear that HIV-1 successfully evades nnAbs responses by keeping its Env in a “closed” conformation ( Bruel et al, 2017 ; Dufloo et al, 2020 ; Veillette et al, 2014 , 2015 ; von Bredow et al, 2016 ), new strategies are currently being tested to harness their potential antiviral activity. Small CD4 mimetic compounds have been optimized to “open up” Env trimers, therefore exposing otherwise occluded epitopes recognized by nnAbs ( Ding et al, 2019b ; Fritschi et al, 2021 ; Jette et al, 2021 ; Laumaea et al, 2020 ; Melillo et al, 2016 ). Using this strategy, CD4mc were shown to synergize with monoclonal CD4i Abs or nnAbs found in plasma from infected individuals to eliminate HIV-1-infected cells in vitro , ex vivo , and in vivo in humanized mice ( Alsahafi et al, 2019 ; Anand et al, 2019 ; Ding et al, 2016b ; Lee et al, 2015 ; Madani et al, 2018 ; Prévost et al, 2020b ; Rajashekar et al, 2021 ; Richard et al, 2015 , 2016 , 2017 ).…”
Section: Resultsmentioning
confidence: 99%